2020
DOI: 10.3390/nu12103026
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Sulforaphane as a Potent BACE1 Inhibitor Based on Kinetics and Computational Studies

Abstract: BACE1 is the rate-limiting enzyme involved in the production and deposition of β-amyloid (Aβ). Since neurotoxic Aβ plays a critical role in Alzheimer’s disease (AD) pathogenesis, BACE1 has emerged as a key target for preventing AD. In the present study, the potential of sulforaphane, an isothiocyanate found in cruciferous vegetables, as a BACE1 inhibitor has been investigated. Sulforaphane exhibited six times more potent activity against BACE1 compared to well-known positive controls including resveratrol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…PD [159][160][161], HD [162], AD [163][164][165][166], MS [167], FRDA [168] BACE1 [169], NF-κB [170] Tertbuthyl-hydroquinene (tBHQ) Activation (Nrf2 branch) HD [171], AD [172], PD [173] Acetylenic tricyclic bis(cyanoenone) TBE-31 Activation (Nrf2 branch-binds KEAP1, thus releasing Nrf2)…”
Section: Perk Pathway Activationmentioning
confidence: 99%
“…PD [159][160][161], HD [162], AD [163][164][165][166], MS [167], FRDA [168] BACE1 [169], NF-κB [170] Tertbuthyl-hydroquinene (tBHQ) Activation (Nrf2 branch) HD [171], AD [172], PD [173] Acetylenic tricyclic bis(cyanoenone) TBE-31 Activation (Nrf2 branch-binds KEAP1, thus releasing Nrf2)…”
Section: Perk Pathway Activationmentioning
confidence: 99%
“…Indeed, Nrf2/ARE regulates the expression of β-secretase 1 ( BACE-1 ) involved in Aβ aggregation and consequently in AD [ 48 ]. Moreover, a recent study demonstrated that SFN, according to a dose-dependent mechanism, can inhibit BACE-1 and consequently Aβ aggregation in a more powerful way compared to quercetin and resveratrol used like controls [ 49 ].…”
Section: Effects Of Sulforaphane In Experimental Studies Of Alzheimentioning
confidence: 99%
“…In another study, depletion of Nrf2 increases BACE1 and a BACE1 mRNA-stabilizing antisense RNA (BACE1-AS) expression and Aβ production and worsens cognitive deficits, and suggesting that sulforaphane-mediated Nrf2 activation decreases BACE1 and BACE1-AS expression and Aβ production and ameliorates cognitive deficits in 5×FAD and 3×Tg-AD mice [ 31 ]. On the other hand, kinetics and computational studies on direct sulforaphane effect on BACE1 showed that sulforaphane has selective and non-competitive BACE1 inhibitory activity [ 48 ].…”
Section: Evidence Of Anti-ad Activity Of Sulforaphane In Animals Amentioning
confidence: 99%
“…In this review, pre-clinical biomarkers (1) Aβ, (2) tau, (3) inflammation, (4) oxidative stress, and (5) neurodegeneration were selected based on the pre-symptomatic biomarkers currently being studied and suggested for clinical practices [ 27 , 28 , 29 , 30 ], and the effects and the mechanisms of sulforaphane on them were overviewed ( Figure 1 and Table 2 , Table 3 , Table 4 , Table 5 and Table 6 ). Most importantly, sulforaphane can prevent the production of Aβ and tau [ 9 , 31 , 32 , 34 , 35 , 48 ], which are the main causative factors for AD. Sulforaphane can inhibit AD-associated inflammation [ 9 , 32 , 37 , 38 , 39 , 42 ], oxidative stress [ 9 , 32 , 37 , 40 , 43 ], and neurodegeneration [ 32 , 33 , 35 , 40 , 41 , 43 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation